1994
DOI: 10.1016/s0022-5347(17)32819-7
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Urinary Diversion: An Alternative to Percutaneous Nephrostomy

Abstract: Nephrostomy has been the standard method of urinary diversion when placement of ureteral stents has failed in cancer patients. We describe our early experience with an alternative method of urinary diversion, the subcutaneous urinary diversion. This extra-anatomical urinary diversion was done in 5 patients during a 15-month interval. The diversion is created using a specially designed 7F double pigtail stent. The proximal end of the stent is inserted into the renal pelvis via a percutaneous nephrostomy punctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 3 publications
0
14
0
4
Order By: Relevance
“…As an alternative to permanent nephrostomy, several authors published results of a subcutaneous nephrovesical stent system [15][16][17][18] . Similar to the system described here the cranial end of a closed stent system is placed in the renal pelvis, the distal end is tunneled subcutaneously and inserted into the bladder by suprapubic puncture.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to permanent nephrostomy, several authors published results of a subcutaneous nephrovesical stent system [15][16][17][18] . Similar to the system described here the cranial end of a closed stent system is placed in the renal pelvis, the distal end is tunneled subcutaneously and inserted into the bladder by suprapubic puncture.…”
Section: Discussionmentioning
confidence: 99%
“…The diversion was created using a specially designed 7F double pigtail stent, which they routinely changed at 4-month intervals. They found it to be a safe, effective and an acceptable alternative to nephrostomy drainage that improved quality of life (Lingam et al, 1994). A year later, another small study reported a marked improvement in patients' overall comfort and quality of life following conversion of nephrostomies to EASs using a similar but slightly larger 8.5F stent (Nakada et al, 1995).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Different types of EAS have been developed and used successfully by different authors (Lingam, 1994;Minhas, 1999;Desgrandchamps, 1998a;, Lloyd, 2007). The designs have varied with the materials used, length of stent, diameter of stent and on whether one or composite stent/s are utilized.…”
Section: Stentsmentioning
confidence: 99%
See 2 more Smart Citations